How is Transportation Logistics Performance Impacted by RT, IWT, ST, Labor, Capital under a Perspective of Economics: The Case of Ho Chi Minh, Vietnam - Hanh, Vu Thi Kim (Modern Perspectives of Logistics Transport in Economics: Empirical Studies in Ho Chi Minh, Vietnam Vol. 1, 2021)
The paper focuses on assessing of transportation logistics (TL) consists of three its sub-sectors are Road transportation (RT), Inland Water Transportation (IWT) and Sea Transportation (ST). The approaches of author are to use the Cobb-Douglas production function (Cobb-Douglas) to assess the dependence of TL’s productivity on the using of input which are labour and capital, applying multivariate linear regression function to analyse the influence of GDP growth monthly of RT, IWT, and ST on TL’s GDP growth monthly, and analytical - statistical methods to measure six indicators are number profitable / losses Transportation Enterprises (TEs), total income/ person/year, % of return on sales (ROS), % of return on equity (ROE), and % of return on assets (ROA). The findings are (1) the marginal productivity of TL increases gradually according to input's scale, (2) GDP growth monthly of TL depends on RT, IWT, and ST’s GDP growth monthly, (3) number of losses TEs is 46% - 54% (5,229 - 14,766 units) which is higher than number of profitable TEs as 38% - 42% (4,505 - 11,067 units), (4) % of ROS, % of ROA, and % of ROE are too low roughly 2.7% – 11.2%, (5) total income/ person/ year is actually too small approximately 4,256USD in 2016 to 5,577USD in 2018.